Autoinflammatory diseases: a Latin American multicenter study according to age and sex - Piotto, Daniela Gerent Petry (2024)
Objective: To evaluate autoinflammatory diseases (AID) according to age at diagnosis and sex, and response to therapy in a large population. Methods: This is a cross-sectional observational study of a Latin American registry using a designed web system for data storage, collected between 2015 and 2018. Any altered findings during follow-up were recorded. The forms were translated into Portuguese and Spanish, including demographic, clinical, laboratory, genetic and treatment characteristics. Results: We included 152 patients, 51.3% male and 75% Caucasian. The median age at disease onset was 2.1 years (0-15.6 years) and median age at diagnosis 6.9 years (0-21.9 years); 111 (73%) were children (0-9 years old), and 41 (27%) were adolescents and young adults (AYA) (10-21 years old). Periodic fever, aphthous stomatitis, pharyngitis, and adenitis syndrome (PFAPA) occurred in 46/152 (30%), chronic non-bacterial osteomyelitis (CNO) in 32/152 (21%), and familial Mediterranean fever (FMF) in 24/152 (15.7%). PFAPA was significantly higher in young children than in AYA (38.7% vs. 7.3%, p<0.001), while CNO were lower (13.5% vs. 41.5%, p<0.001). The frequency of females was significantly higher in CNO (28.4% vs. 14.1%, p=0.031) and lower in FMF (8.1% vs. 23.1%, p=0.011). The most used drugs were glucocorticoids, non-steroidal anti-inflammatory drugs (NSAID), and colchicine. Glucocorticoids and colchicine treatment were used in all AID with good to moderate response. However, cryopyrinassociated periodic syndromes (CAPS) seemed unresponsive to glucocorticoids. NSAIDs and methotrexate were the main medications used to treat CNO. Conclusions: Differences among AID patients were observed in the LA population regarding sex and age at disease diagnosis.